3F.006 Truck drivers' perception of road danger in Nepal: a qualitative study. (14th March 2021) - Khadka, Anish; Gautam, Preeti; Joshi, Elisha; Pilkington, Paul; Parkin, John; Joshi, Sunil; Mytton, Julie
Abstract : Background: Nepal is fast expanding its road network, and over 90% of goods are transported by road. Large numbers of truck drivers are therefore exposed to the risk of crashes. We explored the perceptions and experiences of truck drivers and representatives from their professional association regarding road dangers. Understanding crash risk in commercial drivers can contribute to achieving Sustainable Development Goal 3.6. Methods: We conducted semi-structured interviews with 15 truck drivers and a focus group with 9 members of their professional association. The focus group and interviews were audio-recorded, transcribed, translated, and analyzed using thematic analysis. Results: Six themes were identified: unsafe road environment; bad attitude of the road users on road; risky road user behavior; inadequate road safety knowledge among road users; poor accountability of government agencies; and poor safety culture in the trucking industry. The following factors were perceived as contributing to road danger by truck drivers: strong desire of both drivers and passengers to arrive quickly at destinations; haphazard road crossing; vehicle overloading; poorly maintained roads and vehicles; and trip-based payments. Conclusion: Changes at individual, societal, organizational, and governmental levels are needed to improve road safety in Nepal. Key areas for action are education, improved infrastructure, and accountability. Learning Outcomes: The truck drivers were able to identify factors contributing to both general as well as industry-related road safety issues in Nepal. These findings can be shared with their professional association in order to advocate for structural reforms and increased awareness of road safety within the industry.